Role of Protein Arginine Methyltransferases and Inflammation in Muscle Pathophysiology - So, Hyun-Kyung; Kim, Sunghee; Kang, Jong-Sun; Lee, Sang-Jin (Frontiers in Physiology, 2021)
Arginine methylation mediated by protein arginine methyltransferases (PRMTs) is a post-translational modification of both histones and non-histone substrates related to diverse biological processes. PRMTs appear to be critical regulators in skeletal muscle physiology, including regeneration, metabolic homeostasis, and plasticity. Chronic inflammation is commonly associated with the decline of skeletal muscle mass and strength related to aging or chronic diseases, called sarcopenia. In turn, declined skeletal muscle mass and strength can exacerbate chronic inflammation. Thus, understanding the molecular regulatory pathway underlying the crosstalk between skeletal muscle function and inflammation might be essential to intervene muscle pathophysiology. In this review, we will address the current knowledge on the role of PRMTs in skeletal muscle physiology and pathophysiology with the specific emphasis on its relationship with inflammation.